Developing a sensitive HBV genotyping assay for HBV DNA suppressed patients using both DNA and RNA sequencing. Issue 12 (11th July 2020) - Liu, Yang; May, Lindsey; Liu, Xinan; Martin, Ross; Svarovskaia, Evguenia; Gaggar, Anuj; Mo, Hongmei; Feierbach, Becket
Abstract: Hepatitis B virus (HBV) genotypes impact treatment outcomes and disease progression. The current genotyping methods have limitations in patients with low HBV viral load. In this study, a more sensitive assay has been developed for determining the HBV genotype in HBV DNA suppressed patients. Fifty‐five serum samples from 55 chronic hepatitis B patients (HBeAg−, n = 20; HBeAg+, n = 35) across genotypes A to H with long‐term nucleos(t)ide analogs (NAs) treatment were collected. All samples had HBV DNA less than 29 IU/mL. Total nucleic acid (viral DNA and RNA) was extracted and a 341 bp amplicon located at HBV S gene overlapping with reverse transcriptase domain of polymerase (pol/RT) was amplified via real time (RT)‐nested polymerase chain reaction (PCR) followed by population sequencing. HBV genotype was determined by phylogenetic analysis. The assay successfully amplified HBV S/RT gene from 53 of 55 (96.4%) patient serum samples. Phylogenetic analysis demonstrated that the genotypes of all the 53 PCR positive samples matched the historical genotypes as determined by INNO‐LiPA or RT sequence from the corresponding baseline samples. This assay was able to accurately determine HBV genotype irrespective of baseline genotype, HBeAg status, or duration of viral suppression. The ability to determine genotype in virally suppressed patients may facilitate the evaluation of novel treatment agents for HBV in this patient population. Highlights: A sensitive HBV genotyping assay using DNA and RNA sequencing followed by phylogenetic analysis was developed. Fifty three out of 55 patient serum samples with HBV DNA undetectable across genotypes A to H were successfully amplified and genotyped. This assay was able to accurately determine HBV genotype for HBV DNA suppressed patients.